Study on the Application Effect of Fast Track Surgery Care Combined With Continuous Care After Discharge in Patients With Laparoscopic Cholecystectomy - Yu, Jian; Lin, Xiao; Chen, Hong (Frontiers in Surgery, 2022)
Purpose: To explore the application effect of fast track surgery (FTS) care combined with continuous care after discharge in patients with laparoscopic cholecystectomy (LC). Methods: Two hundred patients treated with LC in our hospital from May 2020 to September 2021 were selected and divided into the routine group receiving routine care (n=100) and the combined group receiving FTS care combined with continuous care after discharge (n=100) according to their care methods. We observed the care effect, surgical stress levels [epinephrine, cortisol, Hamilton anxiety scale (HAMA)], postoperative recovery (time to first exhaust, time to first meal, time to first getting out of bed, time to hospitalization), complications, SF-36 scores after discharge, and care satisfaction in both groups. Results: The total efficiency of care in the combined group was better than that in the routine group (P<0.05). At 1d after surgery, the levels of epinephrine and cortisol in both groups were significantly higher than those at 1h before surgery, and the HAMA scores were significantly lower than those at 1h before surgery, and the combined group was lower than the routine group (P<0.05). The time to first exhaustion, time to first meal, time to first getting out of bed, and time to hospitalization were shorter in the combined group than in the routine group (P<0.05). The overall complication rate in the combined group was lower than that in the routine group (P<0.05). The each item of SF-36 scores after discharge were higher in the combined group than in the routine group (P<0.05). The total satisfaction with care was higher in the combined group than in the routine group (P < 0.05). Conclusion: The implementation of FTS care combined with continuous care after discharge in LC patients is ideal, which can significantly reduce the level of surgical stress, accelerate the recovery process and reduce the occurrence of complications, and improve the postoperative quality of life of patients significantly and with high satisfaction, which is worthy of application.